(untitled) (Journal of Biomedical Investigation, 2024)
Background: Microsporidiasis has been reported mostly in patients with Human-Immuno Deficiency Virus (HIV)/AIDS with diarrhoea and in more than 50% of these patients, no enteric pathogen are identifiable. Aim: This study attempted to establish the natural route of human infection of microsporidiasis and study the pathologically induced manifestations in experimentally infected mice. Methods: We isolated microsporidia spores from stool specimens of HIV-infected patients aged 2-61years and experimentally infect Albino mice with these isolates in an attempt to establish the natural route of human infection and study the pathologically induced manifestations in these experimentally infected mice. Seven hundred and fifty stool samples were collected from HIV-infected patients and 375 samples from their non-infected counterparts to determine the prevalence of Microsporidia infection. Chromoptrope 2R and Ficoll-Hipaque techniques were used to isolate Microsporidia spores. Purification of these isolates was conducted using sucrose gradient centrifugation technique. Prednisolone was used to suppress the immune system in the experimental albino mice. Immuno-compromised and immune-competent albino mice were orally, intranasally and intravenously inoculated with 55 spores/10µl in Phosphate Buffer Saline. At intervals of 2, 5, 10, 17 and 28 days post-infection, the infected mice were sacrificed and their internal organs processed for histopathological studies, using heamatoxylin and eosin stain. Results: The prevalence of microsporidia isolates in the stool samples of 750 HIV-infected patients (42.4%) was significantly higher than in the HIV-non-infected subjects (19.2%) (P < 0.05). In the immune-suppressed Albino Mice, pathological damages were induced in the lungs, small intestines, kidneys and livers, unlike in the non-immuno-suppressed group. Oral ingestion and/or intranasal inhalation are considered to be the natural routes of infection because viable microsporidia spores were recovered only from the stools of treated mice which received microsporidia spores inoculums orally and intranasally. Conclusion: Microsporidiasis is prevalent among immuno-compromised (HIV/AIDS) patients and the associations of microsporidiasis with overt pathology in vital internal organs have been demonstrated in the immuno-suppressed mice.